Towards a Portfolio of Climate Resilient Technological Options: Community level participatory adaptive research - International Institute of Rural Reconstruction (2017)
Farmers in the Philippines are already being challenged by climate change. This is often manifested by climate variability (too much rain, periods of drought, extreme weather, etc.). Household livelihoods, income and nutritional well-being are affected adversely. The impacts of climate change are often unique to specific locations and tend to differ considerably, even from community to community. Solutions need to be derived locally and in partnership with local communities and local governments. Both livelihood and climate risks need to be addressed (for different socio-cultural contexts and agro-ecologies). Community-level participatory action help develop adaptive capacities of local communities to address current and future climate risks. Farmers need a range of options that they can choose from. This publication chronicles lessons from the field from the Municipality of Guinayangan, Quezon. This work has been supported by the Department of Agriculture through the Bureau of Agricultural Research (BAR) and the Systems-Wide Climate Change Office (SWCCO) under the Adaptation and Mitigation Initiative in Agriculture (AMIA) Program and CCAFS Southeast Asia.